1994
DOI: 10.1037/0003-066x.49.10.851
|View full text |Cite
|
Sign up to set email alerts
|

Health care reform: The 1993–1994 evolution.

Abstract: Health care costs in the United States continue to increase, as does the number of individuals who lack health care coverage. The magnitude of these critical problems assures that health reform of the health care system will continue to be debated over the next decade. Increasing health care costs are associated with increased complexity of services and a greater number of health care providers. As health costs increase and the number of individuals covered by private insurance decreases, states will face incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Although it is unlikely that this will happen again, psychologists have a unique role to play in the policy arena, and our voice has not been heard. Policy makers need to know more about psychology in general so that they can give needed attention to psychological health issues and appropriate standards of care (Frank & VandenBos, 1994).…”
Section: What Counseling Psychologists Can Domentioning
confidence: 99%
“…Although it is unlikely that this will happen again, psychologists have a unique role to play in the policy arena, and our voice has not been heard. Policy makers need to know more about psychology in general so that they can give needed attention to psychological health issues and appropriate standards of care (Frank & VandenBos, 1994).…”
Section: What Counseling Psychologists Can Domentioning
confidence: 99%
“…Until the mid-1990s, health care costs rose dramatically, with mental health costs rising more rapidly than health care costs in general (Broskowski, 1991). The number of practicing psychologists increased 300% from 1974 to 1994 (Frank & VandenBos, 1994). Redick, Witkin, Atay, and Manderscheid (1992) reported that ambulatory mental health organization expenditures in the United States grew from $388 million in 1969 to $5.3 billion in 1988 (expenditures in per capita constant dollars growing from $1.94 to $4.96).…”
Section: Ethics When Construed Broadly Sheds New Light On Managed Carementioning
confidence: 99%
“…Making such an ethical case may often be quite difficult, given the strong feelings and the different world views and ethical allegiances among therapy stakeholders, but the stakes are very high. As Frank and VandenBos (1994) point out, "psychologists must be involved in policy issues so as to ensure the utilization of psychological knowledge and attention to psychological and behavioral health needs" (p. 851).…”
Section: Social Ethics and Managed Carementioning
confidence: 99%
“…Health maintenance and managed care organizations continue to pursue service provision contracts within university communities, proposing to provide psychological services more efficiently and more cost-effectively than do existing services. These proposals may make counseling centers seem obsolete to university administration (Broskowski, 1995;Frank & VandenBos, 1994;Hersch, 1995).…”
mentioning
confidence: 99%